2019
DOI: 10.1038/s41598-018-38410-9
|View full text |Cite
|
Sign up to set email alerts
|

NMR Analysis on Molecular Interaction of Lignin with Amino Acid Residues of Carbohydrate-Binding Module from Trichoderma reesei Cel7A

Abstract: Lignocellulosic biomass is anticipated to serve as a platform for green chemicals and fuels. Nonproductive binding of lignin to cellulolytic enzymes should be avoided for conversion of lignocellulose through enzymatic saccharification. Although carbohydrate-binding modules (CBMs) of cellulolytic enzymes strongly bind to lignin, the adsorption mechanism at molecular level is still unclear. Here, we report NMR-based analyses of binding sites on CBM1 of cellobiohydrolase I (Cel7A) from a hyper-cellulase-producing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 42 publications
(58 reference statements)
3
31
0
Order By: Relevance
“…NMR analysis of the 13 C-labeled lignin model compounds provided the rst direct evidence for the identi cation of binding atoms in the linear lignin chains. The results were in good agreement with our previous binding site analysis of the protein counterpart, TrCBM1 with MWL [17]. Herein, we provide direct evidence to reveal the interaction sites in the β-O-4 lignin substructure that bind to TrCBM1.…”
Section: Nmr Chemical Shift Perturbation (Csp) Analysis Is a Powerfulsupporting
confidence: 91%
See 3 more Smart Citations
“…NMR analysis of the 13 C-labeled lignin model compounds provided the rst direct evidence for the identi cation of binding atoms in the linear lignin chains. The results were in good agreement with our previous binding site analysis of the protein counterpart, TrCBM1 with MWL [17]. Herein, we provide direct evidence to reveal the interaction sites in the β-O-4 lignin substructure that bind to TrCBM1.…”
Section: Nmr Chemical Shift Perturbation (Csp) Analysis Is a Powerfulsupporting
confidence: 91%
“…binding sites in proteins [16]. We previously performed CSP analysis to identify the binding amino acid residues in TrCBM1 with softwood and hardwood milled wood lignin (MWL) using 15 N-labeled TrCBM1 [17]. The results suggested that the aromatic rings in lignin participated in interactions with amino acid residues in TrCBM1, because the at plane surface including Y5, Y31, and Y32 in TrCBM1 was a main interaction site.…”
Section: Nmr Chemical Shift Perturbation (Csp) Analysis Is a Powerfulmentioning
confidence: 99%
See 2 more Smart Citations
“…Three types of interactions are involved in adsorption of enzyme onto lignin: (i) hydrophobic interactions (Ying et al 2018;Tokunaga et al 2019); (ii) electrostatic interactions (Nakagame et al 2011;Scott et al 2016), and (iii) hydrogen-bonding (Rahikainen et al 2013;Liu et al 2016). The CBDs of T. reesei cellulases, Cel7A and Cel5A were adsorbed onto lignin in significantly high amount (Yarbrough, et al 2015;Liu et al 2016) due to hydrophobic interaction.…”
Section: Interactions Between Enzyme and Materials Surfaces At The Molmentioning
confidence: 99%